Corporate Social Responsibility Collaborative Strategies for Local Communities - M S, Sarmila; R, Zaimah; Lyndon, Novel (International Journal of Engineering and Technology, 2018)
The concept of Corporate Social Responsibility (CSR) has been identified as an early concept that provides a platform for corporations and community relationship. It is also being discussed that through CSR initiatives corporations would be able to assist in community development efforts. However, to achieve this objective, CSR strategies were required to be implemented according to the needs for community development. This paper will discuss how corporate and community relations through CSR strategies are being implemented for this purpose. The research was conducted on a qualitative case study on a CSR contract farming project by a multinational corporation towards the local farmers' community in Pasir Puteh, Kelantan, Malaysia. A total of 45 farmers who were involved in the project were interviewed. Verbatim data were analyzed to develop themes that could help to provide an understanding of the implementation strategy based on the perspective of the farmers as the recipients of the project. This study has identified the roles played by each of the parties involved based on 38 basic themes emerged from the analysis. These basic themes have been clustered into seven main themes (MT), namely MT1 - Strong Farmers Relationships, MT2 - Support by LFA, MT3 - Positive Attitude of Farmers, MT4 - Farmers Initiative, MT5 - Guaranteed Markets by Corporations, MT6 - Leadership of LFA and MT7 - Learning Process. These themes indicated that the implementation of the CSR project by the corporations was executed in collaboration with the relevant development agency that is the Local Farmers Association (LFA) with the farmer's active involvement. This project is seen to be executed as Public-Private Partnership approach and has assisted the local farmers' community to develop components of community development through the development of skills, attitudes and opportunities for the larger market.
Keywords: CSR and Community; Collaboration Effort; Qualitative Case Study